Hydrogen fluoride adsorbents, methods of making and using the same, and use of spent adsorbents as fluoride electrode materials
Patent Information
- Application Number
- CN202610849701.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-12
- Publication Date
- 2026-09-01
AI Technical Summary
但吸附剂饱和后同样无法进行二次元利用
[0018] In summary, this invention addresses the large amount of decaying oak (Cyclobalanopsis myrsinifolia) waste generated after the harvesting of Gastrodia elata. Through anaerobic fermentation, vacuum micro-oxygen pyrolysis, active metal modification, and calcination, a high-performance hydrogen fluoride (HF) adsorbent with a hierarchical porous structure and abundant metal element dispersion is prepared. Utilizing the adsorbent's efficient HF gas capture capability, HF tail gas from the electrolytic aluminum smelting industry is used as a fluorine source. Under mild conditions, the adsorbed HF reacts and combines with highly dispersed metal active sites to generate nanoscale metal fluorides, which are uniformly loaded onto a carbon framework, ultimately yielding a carbon/metal fluoride composite electrode material. This invention not only achieves high-value utilization of decaying Gastrodia elata wood and synergistic treatment of HF waste gas, but also results in a composite material that combines the buffering effect of a highly conductive carbon network with the high theoretical specific capacity of metal fluorides. When used as a cathode in lithium/sodium-ion batteries, it exhibits excellent cycle stability and rate performance, providing a novel pathway for the functional transformation of biomass waste and the preparation of high-performance energy storage materials.
Smart Images

Figure CN122665573A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of industrial flue gas purification and solid waste resource utilization, specifically involving hydrogen fluoride adsorbents, their preparation methods and applications, and the application of waste adsorbents as fluoride electrode materials. Background Technology
[0002] HF gas is widely generated in industrial production processes such as metallurgy, chemical industry, photovoltaics, and electroplating. It is a highly toxic and corrosive air pollutant. Direct emission of fluorine-containing waste gas not only causes serious air pollution and corrosion of production equipment, but also enters soil and water bodies through sedimentation, disrupting the balance of ecosystems and harming crop growth and human health. Currently, commonly used HF treatment methods in the industrial field include alkaline neutralization, water washing absorption, and adsorption using ordinary carbon materials. Alkaline neutralization consumes a large amount of reagents and generates a large amount of fluoride-containing waste residue and liquid after treatment, which can easily cause secondary pollution. Water washing absorption has limited applicability, insufficient waste gas treatment, and difficulty in meeting stringent emission requirements. Conventional commercial activated carbon adsorbents have fixed pore structures and a limited number of surface active sites, resulting in low adsorption selectivity and saturation adsorption capacity for hydrogen fluoride. They also exhibit poor adsorption stability under complex operating conditions, are difficult to regenerate and reuse, and have high overall treatment costs. Furthermore, adsorbents saturated with HF cannot be reused, easily causing secondary pollution. Existing treatment technologies all have significant shortcomings in application.
[0003] Related technology 1 discloses a method for preparing an adsorbent for selectively adsorbing HF and HCl in SO2 flue gas. This method can efficiently and selectively adsorb HF and HCl in an SO2 atmosphere with a large adsorption capacity, but the adsorbent cannot be reused. Related technology 2 discloses an Al2O3-based adsorbent for HF adsorption and its preparation method. Through precise formulation and process control, the adsorption rate of the Al2O3-based adsorbent for trace amounts of HF is improved. However, once the adsorbent is saturated, it also cannot be reused.
[0004] In summary, the adsorbents for HF gas disclosed in the prior art cannot be reused while maintaining a high adsorption rate, resulting in high adsorbent preparation costs. Summary of the Invention
[0005] The purpose of this invention is to provide a hydrogen fluoride adsorbent, its preparation method and application, as well as the application of waste adsorbent as a fluoride electrode material. The hydrogen fluoride adsorbent provided by this invention has a high adsorption rate for HF, and the saturated waste adsorbent can be reused as a fluoride electrode material. It also exhibits excellent cycle stability and rate performance. This invention provides a new path for the functional transformation of biomass waste and the preparation of high-performance energy storage materials, while reducing the cost of HF adsorbents, and has broad practical application value.
[0006] To achieve the above objectives, the present invention provides the following technical solution: This invention provides a method for preparing a hydrogen fluoride adsorbent, comprising the following steps: Decayed oak wood was subjected to anaerobic fermentation and vacuum micro-oxygen pyrolysis treatment in sequence to obtain a porous biochar carrier. The vacuum degree of the vacuum micro-oxygen pyrolysis treatment was ≤0.05MPa and the oxygen volume concentration was ≤500ppm. The porous biochar carrier had carbon defects. The porous biochar carrier is loaded with a metal precursor by an impregnation method to obtain a semi-finished product. The semi-finished product is calcined in a protective gas atmosphere to obtain the hydrogen fluoride adsorbent. The hydrogen fluoride adsorbent includes a porous biochar support and metal nanoparticles supported on the porous biochar support. The metal nanoparticles are dispersed and include one or more of Fe, Co, Ni, Mn, Cu, V and Ti.
[0007] Preferably, the anaerobic fermentation treatment includes the following steps: mixing the decayed oak wood, yeast, anionic surfactant and water to obtain a suspension; and subjecting the suspension to anaerobic fermentation under anaerobic or oxygen-limited conditions to obtain fermentation products.
[0008] Preferably, the decayed oak wood is the discarded growth substrate wood after the cultivation and harvest of Gastrodia elata, and the wood structure of the decayed oak wood has been partially or completely naturally decomposed; the anionic surfactant is sodium dodecylbenzene sulfonate; the mass percentage of the yeast in the decayed oak wood is 1-15%, and the mass percentage of the anionic surfactant in the decayed oak wood is 0.01-1%; the anaerobic fermentation is carried out under sealed conditions, and the conditions for anaerobic fermentation include: a fermentation temperature of 25-55℃ and a fermentation time of 1-15 days.
[0009] Preferably, before the anaerobic fermentation process yields the fermentation product, the process further includes drying the fermentation product at a temperature of 60-110°C for 12-48 hours. The conditions for the vacuum micro-aerobic pyrolysis treatment include: a vacuum degree of 0.01-0.05 MPa, an oxygen volume concentration of 50-500 ppm, and a pyrolysis space velocity of 300-8000 h⁻¹. -1 The pyrolysis temperature is 300~800℃.
[0010] Preferably, the impregnation method includes the following steps: mixing an aqueous dispersion of the porous biochar support and a solution of a metal precursor to obtain a mixed solution; removing the solvent from the mixed solution to obtain the semi-finished product; the metal precursor includes one or more of Mn(NO3)2, Cu(NO3)2, Ni(NO3)2, Co(NO3)2, Fe(NO3)3, V(NO3)3, and Ti(NO3)4; the semi-finished product includes a porous biochar support and a metal precursor loaded on the porous biochar support, wherein the metal precursor accounts for 1-10% of the mass of the porous biochar support by the mass of metal atoms; the protective gas is nitrogen; the calcination temperature is 300-500℃ and the time is 1-10h; the particle size of the metal nanoparticles is 2-20nm.
[0011] The present invention provides a hydrogen fluoride adsorbent prepared by the preparation method described in the above technical solution.
[0012] This invention provides the application of the hydrogen fluoride adsorbent described in the above technical solution in the treatment of HF tail gas.
[0013] This invention provides a method for treating fluorinated flue gas. The method employs the hydrogen fluoride adsorbent described in the above technical solution to adsorb HF from the fluorinated flue gas, resulting in purified flue gas and waste adsorbent. The waste adsorbent comprises a porous biochar support and metal fluoride nanoparticles loaded on the porous biochar support. The metal fluoride nanoparticles are dispersed and include one or more of FeF3, CoF2, NiF2, MnF3, CuF2, VF3, and TiF4.
[0014] Preferably, after obtaining the waste adsorbent, the method further includes using the waste adsorbent as an electrode for preparing energy storage materials using fluoride electrode materials.
[0015] This invention provides an application of waste adsorbent as a fluoride electrode material in the preparation of energy storage material electrodes, wherein the waste adsorbent is obtained by the treatment method described in the above technical solution.
[0016] This invention provides a method for preparing a hydrogen fluoride adsorbent using decayed oak wood (a substrate for Gastrodia elata) and then using it to prepare an energy storage material electrode. The method involves using the hydrogen fluoride adsorbent described above to adsorb HF from fluorine-containing flue gas, resulting in purified flue gas and waste adsorbent. The waste adsorbent is then used as a fluoride electrode material to prepare an energy storage material electrode.
[0017] This invention provides a method for preparing a hydrogen fluoride adsorbent, comprising the following steps: subjecting decayed oak wood to anaerobic fermentation and vacuum micro-oxygen pyrolysis treatment sequentially to obtain a porous biochar carrier, wherein the vacuum degree of the vacuum micro-oxygen pyrolysis treatment is ≤0.05MPa and the oxygen volume concentration is ≤500ppm, and the porous biochar carrier has carbon defects (C defects); loading a metal precursor onto the porous biochar carrier using an impregnation method to obtain a semi-finished product; calcining the semi-finished product in a protective gas atmosphere to obtain the hydrogen fluoride adsorbent, wherein the hydrogen fluoride adsorbent comprises a porous biochar carrier and metal nanoparticles loaded on the porous biochar carrier, wherein the metal nanoparticles are dispersed and include one or more of Fe, Co, Ni, Mn, Cu, V, and Ti. This invention uses decayed oak wood (the oak wood substrate for Gastrodia elata growth) as raw material. The biomass components are decomposed through anaerobic fermentation, followed by vacuum micro-aerobic pyrolysis to prepare a porous biochar carrier rich in hydroxyl groups and possessing multiple carbon defects. Then, a metal precursor is anchored to the carbon defect sites of the porous biochar carrier via impregnation. A highly dispersed metal active site catalytic system is constructed through calcination, promoting the formation of highly dispersed metal nanoparticles, thereby obtaining a high-performance HF adsorbent. The hydrogen fluoride adsorbent provided by this invention reacts with HF-containing gas. The highly dispersed active metal nanoparticles on the surface of the hydrogen fluoride adsorbent react with HF to generate metal fluorides in situ. After adsorption saturation, the waste adsorbent is obtained, thus yielding a composite electrode material with biochar-supported metal fluorides as its core.
[0018] In summary, this invention addresses the large amount of decaying oak (Cyclobalanopsis myrsinifolia) waste generated after the harvesting of Gastrodia elata. Through anaerobic fermentation, vacuum micro-oxygen pyrolysis, active metal modification, and calcination, a high-performance hydrogen fluoride (HF) adsorbent with a hierarchical porous structure and abundant metal element dispersion is prepared. Utilizing the adsorbent's efficient HF gas capture capability, HF tail gas from the electrolytic aluminum smelting industry is used as a fluorine source. Under mild conditions, the adsorbed HF reacts and combines with highly dispersed metal active sites to generate nanoscale metal fluorides, which are uniformly loaded onto a carbon framework, ultimately yielding a carbon / metal fluoride composite electrode material. This invention not only achieves high-value utilization of decaying Gastrodia elata wood and synergistic treatment of HF waste gas, but also results in a composite material that combines the buffering effect of a highly conductive carbon network with the high theoretical specific capacity of metal fluorides. When used as a cathode in lithium / sodium-ion batteries, it exhibits excellent cycle stability and rate performance, providing a novel pathway for the functional transformation of biomass waste and the preparation of high-performance energy storage materials.
[0019] Therefore, this invention can efficiently remove low-concentration HF from electrolytic aluminum flue gas while completely avoiding secondary pollution caused by the saturation and disposal of traditional adsorbents. This invention achieves a closed-loop function for the adsorbent by converting "pollutants" into "precursors," rather than eliminating them as end-point waste. Furthermore, this invention uses agricultural and forestry waste as raw materials to prepare biochar, which can effectively reduce catalyst costs and realize the resource utilization of solid waste, thus providing an efficient, low-cost, and environmentally friendly technical solution for catalytic reaction systems such as pollutant degradation and energy conversion. Attached Figure Description
[0020] Figure 1 The XRD patterns of the HF adsorbent before and after adsorption provided by this invention; Figure 2 The HF removal efficiency of the HF adsorbent provided by this invention is determined under the following reaction conditions: GHSV = 30000 h⁻¹ -1 The temperature was 50℃ and the HF concentration was 100 mg / L; Figure 3 The open-circuit voltage curves of the HF adsorbent before and after adsorption provided in Example 1 of this invention; Figure 4 Linear scanning voltammetric curves of the HF adsorbent provided in Example 1 of this invention before and after adsorption. Detailed Implementation
[0021] This invention provides a method for preparing a hydrogen fluoride adsorbent, comprising the following steps: Decayed oak wood was subjected to anaerobic fermentation and vacuum micro-oxygen pyrolysis treatment in sequence to obtain a porous biochar carrier. The vacuum degree of the vacuum micro-oxygen pyrolysis treatment was ≤0.05MPa and the oxygen volume concentration was ≤500ppm. The porous biochar carrier had carbon defects. The porous biochar carrier is loaded with a metal precursor by an impregnation method to obtain a semi-finished product. The semi-finished product is calcined in a protective gas atmosphere to obtain the hydrogen fluoride adsorbent. The hydrogen fluoride adsorbent includes a porous biochar support and metal nanoparticles supported on the porous biochar support. The metal nanoparticles are dispersed and include one or more of Fe, Co, Ni, Mn, Cu, V and Ti.
[0022] In this invention, unless otherwise specified, all raw materials / components used in the preparation are commercially available products well known to those skilled in the art.
[0023] This invention involves subjecting decayed oak wood to anaerobic fermentation and vacuum micro-aerobic pyrolysis sequentially to obtain a porous biochar carrier. The vacuum degree of the vacuum micro-aerobic pyrolysis treatment is ≤0.05 MPa, and the oxygen volume concentration is ≤500 ppm. The porous biochar carrier exhibits carbon defects. In this invention, the porous biochar carrier is rich in hydroxyl groups.
[0024] In this invention, the decayed oak wood (Cyclobalanopsis myrsinifolia) is preferably waste oak wood. Specifically, it is preferably decayed wood from the growth substrate discarded after harvesting Gastrodia elata cultivation. The woody structure of the decayed oak wood has partially or completely decomposed naturally. The decayed oak wood is fragmented. Before carrying out the anaerobic fermentation treatment, this invention preferably involves crushing the decayed oak wood to obtain fragmented decayed oak wood. This invention does not have specific requirements for the specific implementation method of the crushing treatment.
[0025] In this invention, the anaerobic fermentation treatment is preferably carried out under anaerobic or oxygen-limited conditions. This invention optimizes the fermentation temperature and time of the anaerobic fermentation treatment to promote the decomposition of biomass cellulose and hemicellulose and to form a porous structure in the decayed oak wood raw material. In this invention, the anaerobic fermentation treatment preferably includes the following steps: mixing the decayed oak wood, yeast, anionic surfactant, and water to obtain a suspension; and subjecting the suspension to anaerobic fermentation under anaerobic or oxygen-limited conditions to obtain a fermentation product. In this invention, the anionic surfactant is preferably sodium dodecylbenzenesulfonate. The percentage of yeast by mass of the decayed oak wood is preferably 1-15%, more preferably 5-10%, and in the examples, it can be 1%, 2%, 5%, 8%, or 10%. The percentage of anionic surfactant by mass of the decayed oak wood is preferably 0.01-1%, more preferably 0.01-0.8%, and even more preferably 0.01-0.5%, and in the examples, it can be 0.01%, 0.02%, 0.05%, 0.1%, or 0.5%. The water can be deionized water. This invention does not have specific requirements regarding the amount of water used, as long as the anaerobic fermentation proceeds smoothly. Mixing is carried out under stirring conditions, and the stirring time can be 1-2 hours. The anaerobic fermentation is carried out under sealed conditions. The preferred conditions for anaerobic fermentation include: a fermentation temperature of 25-55℃ and a fermentation time of 1-15 days.
[0026] In this invention, before the anaerobic fermentation process yields the fermentation product, the invention preferably further includes sequentially subjecting the fermentation product to solid-liquid separation and drying. The solid-liquid separation can be filtration. The solid product obtained from the solid-liquid separation is then dried. The drying process can be oven drying. The preferred drying temperature is 60-110°C, and the preferred time is 12-48 hours.
[0027] In this invention, the dried product undergoes vacuum micro-oxygen pyrolysis treatment. The preferred conditions for the vacuum micro-oxygen pyrolysis treatment include: a vacuum degree of 0.01~0.05 MPa, an oxygen volume concentration of 50~500 ppm, and a pyrolysis space velocity of 300~8000 h⁻¹. -1 The preferred pyrolysis temperature is 300~800℃.
[0028] This invention utilizes vacuum micro-oxygen pyrolysis treatment, optimizing the conditions of this treatment to obtain a porous biochar support with multiple carbon defects. These multiple carbon defects are vacancies formed in the carbon network due to incomplete oxidation or selective removal of oxygen-containing functional groups.
[0029] The present invention preferably obtains a porous biochar carrier rich in carbon defects by adjusting the mass ratio of yeast, sodium dodecylbenzenesulfonate and decayed oak wood, as well as the O concentration and vacuum degree during pyrolysis, so as to provide abundant anchoring sites for metal atoms, and obtain a high energy density electrode material after the active sites fully react with HF.
[0030] After obtaining the porous biochar support, the present invention loads the porous biochar support with a metal precursor by impregnation method to obtain a semi-finished product.
[0031] In this invention, the impregnation method preferably includes the following steps: mixing an aqueous dispersion of the porous biochar carrier and a solution of a metal precursor to obtain a mixed solution; removing the solvent from the mixed solution to obtain the semi-finished product. The aqueous dispersion of the porous biochar carrier is preferably prepared by dispersing the porous biochar with water. The water can be deionized water. The solution of the metal precursor is preferably an aqueous solution of the metal precursor. The metal precursor preferably includes one or more of Mn(NO3)2, Cu(NO3)2, Ni(NO3)2, Co(NO3)2, Fe(NO3)3, V(NO3)3, and Ti(NO3)4, more preferably one or more of Mn(NO3)2, Cu(NO3)2, Ni(NO3)2, Co(NO3)2, and Fe(NO3)3. This invention uses one or more of Mn(NO3)2, Cu(NO3)2, Ni(NO3)2, Co(NO3)2, and Fe(NO3)3 as precursors, resulting in waste adsorbents with superior electrochemical performance as fluoride electrode materials. The mixing is carried out under stirring conditions, with the stirring time preferably being 1-2 hours. The solvent removal preferably includes sequential evaporation and drying. The evaporation can be rotary evaporation. The evaporation temperature is preferably 65-90°C. This invention removes excess moisture through evaporation to obtain a solid product. The drying temperature is preferably 100-105°C, and the drying time is preferably 12-24 hours.
[0032] In this invention, the semi-finished product preferably comprises a porous biochar carrier and a metal precursor loaded on the porous biochar carrier. The metal precursor preferably accounts for 1 to 10% of the mass of the porous biochar carrier by weight of metal atoms, more preferably 2 to 8%, and in the embodiments, it can be 5%.
[0033] After obtaining the semi-finished product, the present invention calcines the semi-finished product in a protective gas atmosphere to obtain the hydrogen fluoride adsorbent. The hydrogen fluoride adsorbent comprises a porous biochar support and metal nanoparticles supported on the porous biochar support. The metal nanoparticles are dispersed and include one or more of Fe, Co, Ni, Mn, Cu, V, and Ti, more preferably one or more of Fe, Co, Ni, Mn, and Cu. In the present invention, the protective gas is preferably nitrogen. The calcination temperature is preferably 300~500℃, more preferably 400℃; the calcination time is preferably 1~10h, more preferably 2~8h, and in the examples, it can be 5h.
[0034] In this invention, the preferred particle size of the metal nanoparticles is 2-20 nm. After loading the metal precursor onto the porous biochar support, a semi-finished product is obtained, which is then calcined. This invention constructs highly dispersed metal nanoparticles through calcination in a protective gas atmosphere, thereby forming a highly dispersed metal active site catalytic system and improving the adsorption rate of HF by the hydrogen fluoride adsorbent.
[0035] The present invention provides a hydrogen fluoride adsorbent prepared by the preparation method described in the above technical solution.
[0036] This invention provides the application of the hydrogen fluoride adsorbent described in the above technical solution in the treatment of HF tail gas.
[0037] In this invention, the HF tail gas contains HF. The HF tail gas may also contain gases other than HF. In this invention, the HF tail gas can be HF tail gas from the electrolytic aluminum smelting industry.
[0038] In this invention, the preferred conditions for the application include: a reaction temperature of room temperature to 150°C, more preferably 80°C to 150°C; a reaction time of 0.5 to 24 h; and a gas hourly space velocity (GHSV) of 30,000 to 50,000 h⁻¹. -1 The concentration of HF in the HF exhaust gas is preferably 1~100 mg / L.
[0039] This invention provides a method for treating fluorinated flue gas. The method employs the hydrogen fluoride adsorbent described in the above-mentioned technical solution to adsorb HF from the fluorinated flue gas, resulting in purified flue gas and waste adsorbent. The waste adsorbent comprises a porous biochar support and metal fluoride nanoparticles loaded on the porous biochar support. The metal fluoride nanoparticles are dispersed and include one or more of FeF3, CoF2, NiF2, MnF3, CuF2, VF3, and TiF4, more preferably one or more of FeF3, CoF2, NiF2, MnF3, and CuF2. Waste adsorbents formed from one or more of FeF3, CoF2, NiF2, MnF3, and CuF2 exhibit superior electrochemical performance as fluoride electrode materials. The metal fluoride nanoparticles are uniformly dispersed in nanoparticle form on the porous biochar support.
[0040] In this invention, during adsorption, the reaction temperature between the hydrogen fluoride adsorbent and HF is room temperature to 150°C, more preferably 80 to 150°C, and the reaction time is preferably 0.5 to 24 hours. In this invention, the fluorinated flue gas can be HF tail gas from the electrolytic aluminum smelting industry.
[0041] In this invention, after obtaining the waste adsorbent, the method further includes using the waste adsorbent as an electrode for preparing energy storage materials using fluoride electrode materials.
[0042] In this invention, the preferred method for preparing the electrode of the energy storage material includes: preparing the waste adsorbent into an electrode slurry and coating it onto a current collector to obtain the electrode of the energy storage material. The current collector is preferably carbon paper. In this invention, the preferred method for preparing the electrode slurry includes: dispersing the waste adsorbent, solvent, and perfluorinated resin solution (Nafion solution) under ultrasonic conditions to obtain the electrode slurry. The solvent preferably includes isopropanol and water, and the volume ratio of isopropanol to water is preferably 3:2. The preferred ratio of the amount of waste adsorbent, solvent, and Nafion solution is 5 mg:970 μL:30 μL.
[0043] This invention provides an application of waste adsorbent as a fluoride electrode material in the preparation of energy storage material electrodes, wherein the waste adsorbent is obtained by the treatment method described in the above technical solution.
[0044] In this invention, the energy storage material electrode can be the positive electrode of an alkali metal ion battery. The alkali metal ion battery preferably includes a lithium-ion battery or a sodium-ion battery.
[0045] This invention provides a method for preparing a hydrogen fluoride adsorbent using decayed oak wood (a substrate for Gastrodia elata) and then using it to prepare an energy storage material electrode. The method involves using the hydrogen fluoride adsorbent described above to adsorb HF from fluorine-containing flue gas, resulting in purified flue gas and waste adsorbent. The waste adsorbent is then used as a fluoride electrode material to prepare an energy storage material electrode.
[0046] In this invention, the waste adsorbent serves as a biochar-supported metal fluoride composite electrode material, possessing a high theoretical capacity and exhibiting excellent cycle stability and rate performance.
[0047] To further illustrate the present invention, the technical solutions provided by the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0048] Example 1 This invention provides a method for preparing a high-performance HF adsorbent and simultaneously synthesizing metal fluoride electrode materials using *Gastrodia elata* growing substrate *Quercus glauca* wood rotten wood, comprising the following steps: (1) Take 100g of decayed oak wood discarded after the cultivation and harvest of Gastrodia elata, crush it and set it aside; add 5g of yeast and 1g of sodium dodecylbenzenesulfonate to 100 mL of deionized water and mix. Stir at room temperature for 2 h to form a suspension. Seal and store at 35℃ for 7 days to complete anaerobic fermentation.
[0049] (2) Filter the fermentation material obtained in (1), and dry the solid product obtained by filtration at 110℃ for 12h.
[0050] (3) The sample obtained in (2) was subjected to a vacuum of 0.05 MPa, an oxygen volume concentration of 50 ppm, and a pyrolysis space velocity of 8000 h⁻¹. -1 Under the given conditions, the temperature was raised to 400℃ and held for 3 hours. After cooling, a porous biochar carrier rich in carbon defects was obtained.
[0051] (4) Take 2.5 g of porous biochar carrier obtained in (3) and stir it with deionized water to form a suspension. Add Cu(NO3)2 aqueous solution and control the Cu atom loading to 5% of the mass of porous biochar carrier. Stir at room temperature for 2 h.
[0052] (5) The suspension obtained in (4) was evaporated at 65°C to remove water, and then dried at 105°C for 12 h.
[0053] (6) All samples from (5) were calcined at 400°C for 3 hours under a nitrogen atmosphere to obtain a high-performance HF adsorbent, denoted as 5Cu / AC-F-400.
[0054] (7) The adsorbent obtained in (6) was used for the purification of HF-containing tail gas from aluminum electrolysis. The reaction conditions were: gas space velocity (GHSV) of 30,000 h⁻¹. -1 Temperature 50℃, HF concentration 100 mg / L.
[0055] (8) After HF adsorption reaches saturation, i.e., the material obtained in (6) cannot effectively adsorb HF, resulting in waste adsorbent; take 5 mg of waste adsorbent, add 970 μL of a mixed solution of isopropanol and water (volume ratio 3:2), add 30 μL of perfluorinated resin solution (Nafion solution), and ultrasonically disperse for more than 30 minutes under ultrasonic conditions. Coat the obtained 100 μL slurry evenly on a 1×1 cm... 2 On carbon paper, a biochar-supported copper fluoride composite electrode positive electrode material was obtained.
[0056] Example 2 This embodiment provides a method for preparing a high-performance HF adsorbent and simultaneously synthesizing a metal fluoride electrode material using *Gastrodia elata* growing substrate *Quercus glauca* wood rotten wood. The difference from Example 1 is that Fe(NO3)3 is used as the metal precursor, and after HF adsorption, FeF3 electrode material can be formed. The specific steps include: (1) Take the decayed oak wood discarded after the cultivation and harvest of Gastrodia elata, crush it and set it aside; add 100g of decayed oak wood, 5g of yeast and 1g of sodium dodecylbenzenesulfonate to 100mL of deionized water and mix. Stir at room temperature for 2 hours to form a suspension. Seal and store at 35℃ for 7 days to complete the anaerobic fermentation.
[0057] (2) Filter the fermentation material obtained in (1), and dry the solid product obtained by filtration at 100°C for 12 hours.
[0058] (3) The sample obtained in (2) was subjected to a vacuum of 0.01 MPa, an oxygen volume concentration of 50 ppm, and a pyrolysis space velocity of 8000 h⁻¹. -1 Under the given conditions, the temperature was raised to 400℃ and held for 3 hours. After cooling, a porous biochar carrier rich in carbon defects was obtained.
[0059] (4) Take 2.5 g of porous biochar carrier obtained in (3) and stir it with deionized water to form a suspension. Add Fe(NO3)3 aqueous solution and control the Fe atom loading to 5% of the mass of porous biochar carrier. Stir at room temperature for 2 h.
[0060] (5) Drying treatment: The suspension was evaporated at 65°C to remove water, and then dried at 105°C for 12 h.
[0061] (6) All samples from (5) were calcined at 400°C for 3 hours under a nitrogen atmosphere to obtain a high-performance HF adsorbent, denoted as 5Fe / AC-F-400.
[0062] (7) The adsorbent obtained in (6) was used for the purification of HF-containing tail gas from aluminum electrolysis. The reaction conditions were: GHSV = 30,000 h. -1 Temperature 50℃, HF concentration 100 mg / L.
[0063] (8) After HF adsorption reaches saturation, i.e., the material obtained in (6) cannot effectively adsorb HF, resulting in waste adsorbent; take 5 mg of waste adsorbent, add 970 μL of a mixed solution of isopropanol and water (volume ratio 3:2), add 30 μL of perfluorinated resin solution (Nafion solution), and ultrasonically disperse for more than 30 minutes under ultrasonic conditions. Coat the obtained 100 μL slurry evenly on a 1×1 cm... 2 On carbon paper, a biochar-supported iron fluoride composite electrode positive electrode material was obtained.
[0064] Example 3 This embodiment provides a method for preparing a high-performance HF adsorbent and simultaneously synthesizing a metal fluoride electrode material using *Gastrodia elata* growing substrate *Quercus glauca* wood rotten wood. The difference from Embodiment 1 is that Co(NO3)2 is used as the metal precursor, and after HF adsorption, a CoF2 electrode material can be formed. The specific steps include: (1) Take the decayed oak wood discarded after the cultivation and harvest of Gastrodia elata, crush it and set it aside; add 100g of decayed oak wood, 5g of yeast and 1g of sodium dodecylbenzenesulfonate to 100mL of deionized water to form a suspension, stir at room temperature for 2 hours, and seal and store at 35℃ for 7 days to complete the anaerobic fermentation.
[0065] (2) Filter the fermentation material obtained in (1), and dry the solid product obtained by filtration at 100°C for 12 hours.
[0066] (3) The sample obtained in (2) was subjected to a vacuum of 0.05 MPa, an oxygen volume concentration of 50 ppm, and a pyrolysis space velocity of 8000 h⁻¹. -1 Under the given conditions, the temperature was raised to 400℃ and held for 3 hours. After cooling, a porous biochar carrier rich in carbon defects was obtained.
[0067] (4) Take 2.5 g of porous biochar carrier obtained in (3) and stir it with deionized water to form a suspension. Add Co(NO3)2 aqueous solution and control the Co atom loading to 5% of the mass of porous biochar carrier. Stir at room temperature for 2 h.
[0068] (5) Drying treatment: The suspension was evaporated at 65°C to remove water, and then dried at 105°C for 12 h.
[0069] (6) All samples from (5) were calcined at 400°C for 3 hours under a nitrogen atmosphere to obtain a high-performance HF adsorbent, denoted as 5Co / AC-F-400.
[0070] (7) The adsorbent obtained in (6) was used for the purification of HF-containing tail gas from aluminum electrolysis. The reaction conditions were: GHSV = 30,000 h. -1 Temperature 50℃, HF concentration 100 mg / L.
[0071] (8) After HF adsorption reaches saturation, i.e., the material obtained in (6) cannot effectively adsorb HF, resulting in waste adsorbent; take 5 mg of waste adsorbent, add 970 μL of a mixed solution of isopropanol and water (volume ratio 3:2), add 30 μL of perfluorinated resin solution (Nafion solution), and ultrasonically disperse for more than 30 minutes under ultrasonic conditions. Coat the obtained 100 μL slurry evenly on a 1×1 cm... 2 Biochar-supported cobalt fluoride composite cathode material was obtained on carbon paper. Test case Figure 1 The XRD patterns of the HF adsorbent provided in Example 1 of this invention before and after adsorption are shown. Figure 1 As shown, the HF adsorbent provided in Example 1 of the present invention forms obvious CuF2 species after adsorbing HF.
[0072] Figure 2 The HF removal efficiency of the HF adsorbents provided in Examples 1, 2, 3 and Comparative Example 1 of this invention was determined under the following reaction conditions: GHSV = 30000 h⁻¹ -1 The temperature was 50℃ and the HF concentration was 100 mg / L. Figure 2The results show that the HF adsorbent provided in Example 1 of this invention can continuously adsorb HF gas with a purification efficiency of over 98% for 7.5 hours. The HF adsorbent provided in Example 2 of this invention can continuously adsorb HF gas with a purification efficiency of over 98% for 6 hours. The HF adsorbent provided in Example 3 of this invention can continuously adsorb HF gas with a purification efficiency of over 98% for 5.5 hours. Ordinary activated carbon can only continuously adsorb HF gas with a purification efficiency of over 98% for 3 hours.
[0073] Figure 3 The data provided in Example 1 of this invention show the open-circuit voltage of the HF adsorbent before and after adsorption. The sample saturated with HF adsorption exhibits a higher open-circuit voltage, indicating that it is more likely to gain electrons, is more easily reduced, and has superior electrochemical performance.
[0074] Figure 4 The linear sweep voltammetric curves of the HF adsorbent provided in Example 1 of this invention before and after adsorption are shown. With increasing voltage, it can be observed that the sample saturated with HF adsorbed exhibits a higher current at the same voltage, confirming that the sample saturated with HF adsorbed in the electrocatalytic reaction system has higher electrochemical reaction activity, and also confirming that the electron transfer capacity of the sample saturated with HF adsorbed is superior to that of the sample without HF adsorption.
[0075] Comparative Example 1: The method is basically the same as that provided in Example 1, except that the pyrolysis in step (3) is carried out under a N2 atmosphere, without vacuuming or introducing O2. The resulting hydrogen fluoride adsorbent product is denoted as 5Cu / ordinary activated carbon.
[0076] Comparison of effects: In the absence of vacuum and micro-oxygen environment, the surface defects of the obtained biochar material are less. After loading Cu, the Cu species particles are larger and the exposed adsorption sites are fewer. The effective adsorption time for HF is reduced to 4 hours. It is not easy to react and form CuF2 during the HF adsorption process and does not have the corresponding electrochemical performance.
[0077] Comparative Example 2: The method is basically the same as that provided in Example 1, except that the oxygen volume concentration under the pyrolysis conditions in step (3) is 1 vol.%.
[0078] Comparison of effects: With higher oxygen concentration, the surface of the resulting biochar material is excessively oxidized, reducing the surface area. After loading Cu, the Cu species particles are larger, with fewer exposed adsorption sites, reducing the effective adsorption time for HF to 2 hours. It is not easy to react and form CuF2 during HF adsorption, and it does not have the corresponding electrochemical performance.
[0079] Comparative Example 3: The method is basically the same as that provided in Example 1, except that the pyrolysis temperature in step (3) is 800°C.
[0080] Comparison of effects: At higher pyrolysis temperatures, nitrogen is released from the resulting biochar material, carbon atoms are reorganized, the crystallinity of the biochar material increases, the surface area decreases, and after loading Cu, the Cu species particles are larger, with fewer exposed adsorption sites, and the effective adsorption time for HF is reduced to 2.5 hours. It is not easy to react and form CuF2 during HF adsorption, and it does not have the corresponding electrochemical performance.
[0081] As demonstrated by the above embodiments, this invention addresses the large amount of decaying oak (Cyclobalanopsis myrsinifolia) waste generated after the harvesting of Gastrodia elata. Through bio-fermentation, vacuum carbonization, micro-oxidation, and active metal modification, a high-performance hydrogen fluoride (HF) adsorbent with a hierarchical porous structure and abundant metal element dispersion is prepared. Utilizing the adsorbent's efficient HF gas capture capability, HF tail gas from the electrolytic aluminum smelting industry is used as a fluorine source. Under mild conditions, the adsorbed HF reacts and combines with highly dispersed metal active sites to generate nanoscale metal fluorides, which are uniformly loaded onto a carbon framework, ultimately yielding a carbon / metal fluoride composite electrode material. This invention not only achieves high-value utilization of decaying Gastrodia elata wood and synergistic treatment of HF waste gas, but also results in a composite material that combines the buffering effect of a highly conductive carbon network with the high theoretical specific capacity of metal fluorides. When used as a cathode in lithium / sodium-ion batteries, it exhibits excellent cycle stability and rate performance, providing a novel pathway for the functional transformation of biomass waste and the preparation of high-performance energy storage materials.
[0082] Although the above embodiments have provided a detailed description of the present invention, they are only some embodiments of the present invention, and not all embodiments. Other embodiments can be obtained based on these embodiments without creative effort, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A method for preparing a hydrogen fluoride adsorbent, characterized in that, Includes the following steps: Decayed oak wood was subjected to anaerobic fermentation and vacuum micro-oxygen pyrolysis treatment in sequence to obtain a porous biochar carrier. The vacuum degree of the vacuum micro-oxygen pyrolysis treatment was ≤0.05MPa and the oxygen volume concentration was ≤500ppm. The porous biochar carrier had carbon defects. The porous biochar support was loaded with a metal precursor by an impregnation method to obtain a semi-finished product. The semi-finished product is calcined in a protective gas atmosphere to obtain the hydrogen fluoride adsorbent. The hydrogen fluoride adsorbent includes a porous biochar support and metal nanoparticles supported on the porous biochar support. The metal nanoparticles are dispersed and include one or more of Fe, Co, Ni, Mn, Cu, V and Ti.
2. The preparation method according to claim 1, characterized in that, The anaerobic fermentation process includes the following steps: mixing the decayed oak wood, yeast, anionic surfactant and water to obtain a suspension; and subjecting the suspension to anaerobic fermentation under anaerobic or oxygen-limited conditions to obtain fermentation products.
3. The preparation method according to claim 2, characterized in that, The decayed oak wood is the discarded growth substrate wood after the cultivation and harvest of Gastrodia elata, and the wood structure of the decayed oak wood has been partially or completely naturally decomposed; the anionic surfactant is sodium dodecylbenzenesulfonate; the mass percentage of the yeast in the decayed oak wood is 1-15%, and the mass percentage of the anionic surfactant in the decayed oak wood is 0.01-1%; the anaerobic fermentation is carried out under sealed conditions, and the conditions for anaerobic fermentation include: fermentation temperature of 25-55℃ and fermentation time of 1-15 days.
4. The preparation method according to any one of claims 1 to 3, characterized in that, The anaerobic fermentation process yields fermentation products. Before the vacuum micro-aerobic pyrolysis treatment, the fermentation products are dried at a temperature of 60-110°C for 12-48 hours. The conditions for the vacuum micro-aerobic pyrolysis treatment include: a vacuum degree of 0.01-0.05 MPa, an oxygen volume concentration of 50-500 ppm, and a pyrolysis space velocity of 300-8000 h⁻¹. -1 The pyrolysis temperature is 300~800℃.
5. The preparation method according to claim 1, characterized in that, The impregnation method includes the following steps: mixing an aqueous dispersion of the porous biochar support and a solution of a metal precursor to obtain a mixed solution; removing the solvent from the mixed solution to obtain the semi-finished product; the metal precursor includes one or more of Mn(NO3)2, Cu(NO3)2, Ni(NO3)2, Co(NO3)2, Fe(NO3)3, V(NO3)3, and Ti(NO3)4; the semi-finished product includes a porous biochar support and a metal precursor loaded on the porous biochar support, wherein the metal precursor accounts for 1-10% of the mass of the porous biochar support by the mass of metal atoms; the protective gas is nitrogen; the calcination temperature is 300-500℃ and the time is 1-10h; the particle size of the metal nanoparticles is 2-20nm.
6. The hydrogen fluoride adsorbent prepared by the preparation method according to any one of claims 1 to 5.
7. The application of the hydrogen fluoride adsorbent according to claim 6 in the treatment of HF tail gas.
8. A method for treating fluorinated flue gas, characterized in that, The hydrogen fluoride adsorbent according to claim 6 is used to adsorb HF in fluorine-containing flue gas to obtain purified flue gas and waste adsorbent; the waste adsorbent includes a porous biochar support and metal fluoride nanoparticles loaded on the porous biochar support, the metal fluoride nanoparticles are dispersed, and the metal fluoride nanoparticles include one or more of FeF3, CoF2, NiF2, MnF3, CuF2, VF3 and TiF4.
9. The processing method according to claim 8, characterized in that, After obtaining the waste adsorbent, the method further includes using the waste adsorbent as an electrode for preparing energy storage materials using fluoride electrode materials.
10. A method for preparing a hydrogen fluoride adsorbent from decayed oak wood (a Gastrodia elata growth substrate) and then using it to prepare an energy storage material electrode, characterized in that... The hydrogen fluoride adsorbent described in claim 6 is used to adsorb HF in fluorine-containing flue gas to obtain purified flue gas and waste adsorbent; the waste adsorbent is used as an electrode to prepare energy storage materials as a fluoride electrode material.